A educação permanente como estratégia de intervenção na identificação do risco de fragilização em pessoas idosas - SOUSA, Evandro Cesar Natividade de (2019)
The present study aimed to identify the profile of the professionals involved, to raise awareness about the importance of identifying fragile elderly and to demonstrate the importance of permanent education as an intervention tool. This is a descriptive research of a qualitative nature. After analyzing the data, there was concern for some answers, leading us to select the ones that are corroborated for the division into four categories, which express the importance of continuing education in the screening of older people, namely: The process of embrittlement linked to impairment of functional capacity, The importance of screening instruments to identify the fragile elderly, The ACS as a link between the community and the health team in identifying the fragile elderly and Challenges for identifying the fragile elderly in Primary Health Care. It was observed initially some deficiencies on the part of the professionals regarding the characterization of the process of embrittlement and its real concepts, as well as the use of instruments for its identification, soon after the capacitations became evident the empowerment on the part of the professionals as the real need to know the process of fragilization in all its dimensions, and the correct way to use the instruments of identification of the fragile elderly, therefore we can affirm that permanent education constitutes an important instrument of transformation, capable of changing realities and thoughts, and promote benefits for the users as well as for the professionals who work in it